Distinct small RNAs are expressed at different stages of Phytophthora capsici and play important roles in development and pathogenesis - Zhong, Shan; Zhang, Sicong; Zheng, Yang; Zhang, Qinghua; Liu, Fangmin; Wang, Zhiwen; Liu, Xili (Frontiers in Genetics, 2024)
Small RNAs (sRNAs) are important non-coding RNA regulators that play key roles in the development and pathogenesis of plant pathogens, as well as in other biological processes. However, whether these abundant and varying sRNAs are involved in Phytophthora development or infection remains enigmatic. In this study, sRNA sequencing of 4 asexual stages of Phytophthora capsici (P. capsici), namely as mycelia (HY), sporangia (SP), zoospores (ZO), cysts (CY), and pepper infected with P. capsici (IN), were performed, followed by sRNA analysis, microRNA (miRNA) identification, and miRNA target prediction. sRNAs were mainly distributed at 25-26 nt in HY, SP,